Extensive reorganization of the chloroplast genome of Corydalis platycarpa: A comparative analysis of their organization and evolution with other Corydalis plastomes - Raman, Gurusamy; Nam, Gi-Heum; Park, SeonJoo (Frontiers in Plant Science, 2022)
The chloroplast (cp) is an autonomous plant organelle with an individual genome that codes for essential cellular functions. The genome architecture and gene content of the cp is highly conserved in angiosperms. The plastome of Corydalis belongs to the Papaveraceae family, and the genome is comprised of unusual rearrangements and gene content. Thus far, no extensive comparative studies have been carried out to understand the evolution of Corydalis chloroplast genomes. Therefore, the Corydalis platycarpa cp genome was sequenced, and wide-scale comparative studies were conducted using publicly available twenty Corydalis plastomes. Comparative analyses showed that an extensive genome rearrangement and IR expansion occurred, and these events evolved independently in the Corydalis species. By contrast, the plastomes of its closely related subfamily Papaveroideae and other Ranunculales taxa are highly conserved. On the other hand, the synapomorphy characteristics of both accD and the ndh gene loss events happened in the common ancestor of the Corydalis and sub-clade of the Corydalis lineage, respectively. The Corydalis-sub clade species (ndh lost) are distributed predominantly in the Qinghai-Tibetan plateau (QTP) region. The phylogenetic analysis and divergence time estimation were also employed for the Corydalis species. The divergence time of all the ndh gene lost Corydalis sub-clade species (44.31 – 15.71 mya) coincides very well with the uplift of the Qinghai-Tibet Plateau in Oligocene and Miocene periods, and maybe during this period, it has probably triggered the radiation of the Corydalis species. To the best of the authors’ knowledge, this is the first large-scale comparative study of Corydalis plastomes and their evolution. The present study may provide insights into the plastome architecture and the molecular evolution of Corydalis species.